Regulacje prawne w zakresie szczepień ochronnych przeciwko COVID-19 – problemy wybrane - Szudejko, Piotr; Jachimowicz-Jankowska, Paulina (Studia Prawa Publicznego, 2021)
Undoubtedly, the end of 2019 will be recorded in the annals of modern human history as a time which resulted in an unprecedented event. This is because this year, the global epidemic of the SARS-CoV-2 virus broke out. This virus, on the other hand, leads to the development of an acute infectious disease of the respiratory tract, known as COVID-19. Therefore, the state of epidemic threat that was initially introduced in Poland, and then transformed into the current epidemic state, requires a particular reaction from the state authorities and also, it would seem, an appropriate response to the situation by the citizens themselves. In such exceptional circumstances, the obligation arises for the state to protect the life and health of its citizens, both in the area of enacting the relevant law and its implementation. However, there is a remedy for the growing number of new cases of COVID-19 and deaths in this context, namely the possibility of performing preventive vaccinations against this disease. This article aims to analyze and evaluate the legal regulations on preventive vaccinations against COVID-19 introduced in Poland. In this regard, reference is made to the basic assumptions used in the constitutional model of health care in Poland. In this context, the principle of equal access to health care services financed from public funds and the constitutional exceptions to the principle of equal access to benefits, such as children, pregnant women, disabled and elderly people are discussed, as well as the principle of the active role of the state in combating epidemic threats. These considerations are complemented by an outline of the statutory and sub-statutory solutions in the health care model. The analysis also covers legal solutions adopted with regard to the COVID-19 epidemic, and presents the distribution of SARS-CoV-2 vaccines as well as restrictions, orders and bans in connection with the epidemic. In addition, the compliance of the distribution of SARS-CoV-2 vaccines with the constitutional model of health protection is assessed, with the criteria for assessing this distribution in the context of establishing the state of the epidemic being singled out.